Whole‐nanoparticle atomistic modeling of the schwertmannite structure from total scattering data. Issue 6 (20th October 2017) - Sestu, M.; Navarra, G.; Carrero, S.; Valvidares, S. M.; Aquilanti, G.; Pérez-Lopez, R.; Fernandez-Martinez, A.
Abstract : A single‐particle structural model of schwertmannite is proposed from a combined multi‐technique approach, using a novel reverse Monte Carlo/Debye scattering equation parallel code. Abstract : Schwertmannite is a poorly crystalline nanometric iron sulfate oxyhydroxide. This mineral shows a structural variability under different environments. Because of that, the determination of its structure and, consequently, of its physical–chemical properties is quite challenging. This article presents a detailed structural investigation of the structure of schwertmannite conducted under different approaches: X‐ray absorption spectroscopy, Rietveld refinement, and a combined reverse Monte Carlo and Debye function analysis of the whole nanoparticle structure. The schwertmannite model presented here is, to the auhors' knowledge, the most complete model so far reported.